Pengawasan Bank Asing di Indonesia - sefriani sefriani (Jurnal Hukum IUS QUIA IUSTUM, 2002)
Indonesia have no institution about foreign bank controlling specifically although the foreign banks have different characteristics from nationai banks. The rule of controlling for foreign banks in Indonesia have been spreading on several regulation for institution.It coud be said however that the regulation and controlling practice forforeign banks in Indonesia today havereferrred to what havebeen assignedBIS to realize forcontrolling of the effective consolidation for rhultinationai banks which have been operating in Indonesia.